Пути улучшения управления проблемными активами банковской системы Украины - Кантур, С.Ф.; Шишкова, А.И. (Культура народов Причерноморья, 2013)
В статье рассматривается сущность и причины возникновения проблемных кредитов, вопросы эффективности внешних методов управления проблемными активами банковской системы Украины, а также мероприятия направленные на оздоровление банковской системы. Ключевые слова: просроченная задолженность по кредитам, проблемные активы, методы управления проблемными активами, коллекторы, факторинговые компании, санационный банк. У статті розглядається сутність та причини виникнення проблемних кредитів, питання ефективності зовнішніх методів управління проблемними активами банківської системи України, а також заходи щодо оздоровлення банківської системи. Ключові слова: прострочена заборгованість за кредитами, проблемні активи, методи управління проблемними активами, колектори, факторингові компанії, санаційний банк. Essence and reasons of origin of problem credits is examined in the article, and questions of efficiency of external methods of management of problem assets of the banking system of Ukraine, and also measures are directed on making healthy of the banking system. Tendencies are analysed in the dynamics of their volume and specific gravity in the structure of credit brief-case of domestic banks, and also volume of the formed backlogs under credit operations and under possible losses to on by him, the different going is probed near a management the problem credits of bank with the purpose of minimization of losses. In the article the modern problems of the bank crediting are analysed and the basic ways of their decision are outlined by the improvement of management of problem assets. Possibility of refunding of problem credits is considered due to bringing in of facilities of institucional'nykh investors, above all things facilities of institutes of the general investing. The prospects of application of internal and external methods of management of assets are considered. For the most rapid reduction of bad assets and increasing the pace of lending to the real economy justified the need for public sanatsiynoho bank or state company managing problem assets. Key words: arrears on loan, troubled assets, methods of problem assets, collectors, factoring companies, sanatsiynyy bank.